UJICOBA PERPADUAN MEDIA TANAM COCOPEAT -TOPSOIL DAN DOSIS PUPUK SP-36 TERHADAP PERTUMBUHAN TANAMAN KEDELAI HITAM MALIKA (GLYCINE SOJA. L) - Sipayung, Patricius; Sitohang, Nurdin; Purba, Andre Hartono (LPPM Universitas Katolik Santo Thomas Medan, 2023)
The research aims to test the media plant cocopeat-top soil as well dose SP-36 fertilizer against growth soya bean black malika (Glycine soja.L ). To know the impact of the growth of oil palm seedlings (Elaesis guineensis Jacq.) in dose using rice husk charcoal biochar on some type of soil in pre- nursery. The research uses the Design Random Factorial (DRF) consist of 2 factors . The first factor is a mixture of cocopeat - top soil planting media . The second one is SP-36 dose . Based on the results of the study, it can be stated that, cocopeat planting media with topsoil had no significant effect on plant height at 4, 5, 6 and 7 mst, significantly affected the number of branches aged 7 and 8 mst and plant root length, but had no significant effect on flowering age, weight of 100 seeds, and number of root nodules. The dose of SP-36 fertilizer had no significant effect on plant height at the ages of 2, 3, 8, 11, 12 and 13 mst, flowering age, weight of 100 seeds and root length, but had no significant effect on number of branches and number of root nodules. The interaction of cocopeat growing media with topsoil and the dose of SP-36 fertilizer had no significant effect on all observed parameters .The dose of SP-36 fertilizer had no significant effect on plant height at 2, 3, 8 11 and 12 mst, flowering age, weight of 100 seeds and root length, but had no significant effect on number of branches and number of root nodules.